A symptom-based classification for shoulders with massive rotator cuff defects - Loew, Markus; Raiss, Patric (International orthopaedics, 2010)
The aim of this prospective study was to propose a classification for shoulders with massive rotator cuff defects based on patients’ clinical symptoms. A total of 100 shoulders with massive rotator cuff tears were evaluated clinically using the Constant score (CS) and with radiographs in two planes. Three types were defined and correlated with radiographic findings: (1) the arthritic type (type I), (2) the non-reactive type (type II) and (3) the necrotic type (type III). Significant differences in the overall CS (type I: 28.6 points, range: 4 - 61; type II: 18.8 points, range: 6 - 52; type III: 15.5 points, range: 6 - 31) and its subgroups and in shoulder motion were found between types I and II and between types I and III (p < 0.05). This classification may be helpful for the decision-making process with regard to the appropriate form of shoulder replacement surgery in patients with massive rotator cuff defects.
Online veröffentlicht am 13. Februar 2009
Gesehen am 29.03.2023